PEMANFAATAN MEDIA SOSIAL FACEBOOK SEBAGAI WASILAH DAKWAH MAHASISWA - Ahmad Adnan; Mastur Lungi (STAI DI AL-HIKMAH, 2022)
The purpose of this study is to determine the utilization of social media up as a Wasilah Dakwah STID Students in Al-Hikmah Angkatan 49. The research method used in this research is qualitative descriptive. Methods of data collection is by depth interview, observation, and documentation. Conclusion of research, facebook utilization as wasilah da'wah by STID students in Al-Hikmah 49 by way of: a) spread positive news about Islam. b) Posting good things in the form of video, pictures and inspirational writings. c) Post something that is good. Sharing good postings of goodness, and actively speaking good in the comment field. d) Write articles of Islam, fiqh, hadith, tafseer etc. e) uploading study videos of the scholars. F) Write the motivation of Islamic da’wah.